Sind Bilder noch Zeichen? Semiotische Sicht auf die Bilder in den modernen Medien - Anna Kapuścińska (Colloquia Germanica Stetinensia, 2018)
The following paper is based on the semiotic approaches, which give pictures the status of signs, and addresses concurrently the problem of the condition of pictures as signs. The discussion in this article ranges from the question of the sign character of traditional and earlier digital pictures, to the question of the contemporary concept of picture and of the sign character of the contemporary pictures, which are present in the modern media.